Priming effects on non-verbal communication and one's perceived performance specific to the job interview - Bloch, Kyle (My University, 2015)
The purpose of this study was to expand the empirical research surrounding non-verbal communication within the employment interview. A cross-sectional experiment was administered at The University of Witwatersrand in order to investigate whether or not confident body language could be primed. 53 Psychology 1 students from WITS volunteered to take part in the study. However the findings revealed insignificant results